Społeczne funkcje szkolnictwa wyższego w RPA i konstruowanie różnicy - Hejwosz-Gromkowska, Daria (Wydawnictwo Naukowe UAM, 2012)
Following the ending of apartheid, the question is asked to what extend the equity between the Blacks, Coloured and Whites was achieved. The large disproportion in school access during the apartheid period caused inequalities and marginalized especially non-Whites. After 1994 many reforms were introduced in the school system to assure equity in education among different ethnic groups. The Blacks and other ethnic groups still have worse results in the school system. The research data show that many of the Blacks still attend to the poor schools where they received worse quality of education, while the Whites have an access to well-equipped schools. Thus the chances of the latter to achieve high position on the social ladder are better. Despite the fact that enrollment in higher education increased among these groups, still many of them do not graduated from the universities and technikons. The researchers also point out that not only race is the most important factor in the social stratifi cation but also socio-economic status. Moreover, some of them see that in the South Africa there is (de)segregation in the school system because of these two mentioned factors. In this paper I made an attempt to reconstruct the social function of the education in post-apartheid era. I also try to answer to the question why there is a gap between school achievement among the Blacks and the Whites. I analyze and discuss the main factors which infl uence to the access to higher education.
Social function of higher education in South Africa and the construction of the difference
Keywords: South Africa; inequalities; higher education; race; socio-economic status